Small-Medium Enterprises (SMEs) Batik Tulis in Jetis Village, District of Sidoarjo - Ong Andre Wahyu Riyanto; Slamet Riyadi; Maya Ida Kusuma (OJS Universitas Muhammadiyah Gresik, 2018)
This activity program aims to increase the efficiency of marketing business management SMEs batik Tulis in Sidoklumpuk village, Jetis Lemahputro, Sidoarjo District. The targets to be achieved for this program, include: 1) creating online commercial sales system to expand access marketing batik product to foreign countries, as well as providing convenience for customers as well as SMEs in conducting business transactions. 2) Creating logo design for the product packaging common local wisdom of kampong batik Jetis to strengthen the brand. So that SMEs are expected to develop into business to meet customer demand and survive in a competitive business climate. The utilization of e-commerce web for SMEs batik around Jetis. Jetis Batik can be a characteristic of great micro business in Jetis Village. The local government is expected to provide support for the success of the SMEs independently initiated programs collectively.